THE BORDER CITY OF TÉBESSA: HISTORICAL DIMENSIONS AND CRITICAL REFLECTION - Sabah Chems Rifi,; Salah Chaouche, (International Journal of Innovative Technologies in Social Science, 2025)
This research engages in a thorough reflection on the city of Tébessa, a city located at the edges of its national territory and marked by a peripheral position, both geographically and symbolically. This reflection is centered around two fundamental and interdependent spatial concepts: "the city" and "the border." The main objective of this study is to examine the historical and contemporary interactions between these two dimensions, focusing on two key aspects: Tébessa's geographical position as a border city and the organization of its road network.The analysis highlights the impact of the historical transformation of the border on the structure and function of the city. In the past, the border had a "zonal" and shifting form, allowing the ancient Theveste to play a central role in cross-border exchanges and interactions. In this context, the city served as a strategic hub, driven by economic, cultural, and social flows. However, with the evolution of borders into a "linear" and fixed form, Tébessa gradually lost its dynamic position, becoming a marginalized city, isolated and self-contained.This transition not only affected Tébessa's identity and development but also reshaped its role in the regional space. Nevertheless, the border should not be seen solely as a constraint; it also represents a strategic opportunity. Indeed, Tébessa's border position could be reinvested to make it a hub for development and cross-border exchanges. With proper planning, the city could reinvent itself as a "transborder metropolis," capable of leveraging its geographical location to enhance its attractiveness, competitiveness, and integration into regional dynamics.Thus, this study emphasizes that the border is not only a line of separation but also a space of potentialities. It can be viewed as a lever to reposition Tébessa with a forward-looking perspective, fostering a synergy between its historical heritage, economic dynamism, and strategic role in cross-border exchanges.